70.1k views
1 vote
Solve for x.

-15 + 12x = 5x + 7 - 3x

User Kerrine
by
4.2k points

2 Answers

4 votes

Steps to solve:

-15 + 12x = 5x + 7 - 3x

~Combine like terms

-15 + 12x = (5x - 3x) + 7

~Simplify

-15 + 12x = 2x + 7

~Add 15 to both sides

-15 + 15 + 12x = 2x + 7 + 15

~Simplify

12x = 2x + 22

~Subtract 2x to both sides

12x - 2x = 2x - 2x + 22

~Simplify

10x = 22

~Divide 10 to both sides

10x/10 = 22/10

~Simplify

x = 11/5 or 2.2

Best of Luck!

User Andriy Shevchenko
by
5.3k points
6 votes

Answer:

x = 2.2

Explanation:

-15 + 12x = 5x + 7 - 3x

Combine like terms

-15 +12x = 2x +7

Subtract 2x from each side

-15 +12x -2x = 2x-2x +7

-15 +10x = 7

Add 15 from each side

-15+15 +10x = 7+15

10x = 22

Divide each side by 10

10x/10 = 22/10

x = 2.2

User NumesSanguis
by
5.1k points